Strategi Indonesia Keluar dari INSG (2006): Analisis Ekonomi Politik dan Hilirisasi Nikel - Sukmatika, Anak Agung Yumas (LITERATUS, 2025)
Indonesia’s decision to withdraw from the International Nickel Study Group (INSG) in 2006 reflects the dynamics of national interests in navigating global resource governance. This study aims to analyze the withdrawal through the lens of international political economy, focusing on the nickel downstreaming policy as a strategy for economic self-reliance. Employing a qualitative approach and document analysis method, the research explores Indonesia’s motivations by examining the context of economic globalization, domestic actor interests, and industrial policy shifts. The findings suggest that the decision was driven not merely by the perceived ineffectiveness of the INSG, but by a broader developmental paradigm shift prioritizing value-added production within global supply chains. The withdrawal from INSG is part of a strategic effort to strengthen Indonesia’s position in global nickel governance and to accelerate its downstreaming agenda. This study also contributes to a deeper understanding of political economy dynamics in natural resource management and the implications for economic sovereignty amid global market pressures.